Identifikasi Extended Spectrum Beta Laktamase (ESBL) Antibiotika Golongan Sefalosporin pada Bakteri Acinetobacter baumannii - Hilmiati Wahid (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Extended Spectrum Beta-Lactamases (ESBL) are group of enzymes that break down the antibiotics of penicillin and cephalosporin group,this enzymes made bacteria are resistant to this type of antibiotic. Acinetobacter baumannii is one of the gram-negative bacteria, produce the ESBL enzyme. Globally, Acinetobacter baumannii has become a nosocomial pathogen that continues to increase in frequency. The prevalence of ESBL of Acinetobacter spp in Indonesia is 19-29% which is resistant to the third and fourth generation cephalosporin antibiotics. This study uses an experimental laboratory design with consecutive sampling techniques. Acinetobacter baumannii was isolated from 50 patients. The isolate comes from sputum, pus, blood, urine, endotrackeal (ETT), pleural fluid, bronchial rinses and stool. Samples of isolates were identified using standard bacteriological methods and the Vitek 2 Compact ® system using a GN card. Tests carried out include antimicrobial sensitivity tests performed using the Kirby-Bauer diffusion method and ESBL production test using the Double Disc Synergy Test (DDST) and Phenotypic Confirmatory Test. The results showed that the bacterium Acinetobacter baumannii was successfully isolated from all samples with an accuracy level (91% - 99%). In the antimicrobial sensitivity test it was found that of the 50 clinical samples tested against antibiotics cephalosporin group, which had experienced resistance in the largest sequence were Cefotaxime 22 samples (44%), Ceftazidime 20 samples (40%), Ceftriaxone 20 samples (40%) and Cefepime 19 samples (38%). In the ESBL production test found 9 samples (18%) positive ESBL in ceftazidime + As.Klavulanat antibiotics, 9 samples (18%) positive ESBL in cefotaxime + As.Klavulanat antibiotics (30 ?g / 10 ?g). Keywords: Cephalosporin antibiotics, Acinetobacter baumannii, Resistance, Extended Spectrum Beta Lactamase (ESBL)